2008
DOI: 10.1186/1754-6834-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Pichia stipitis xylose reductase helps detoxifying lignocellulosic hydrolysate by reducing 5-hydroxymethyl-furfural (HMF)

Abstract: Background: Pichia stipitis xylose reductase (Ps-XR) has been used to design Saccharomyces cerevisiae strains that are able to ferment xylose. One example is the industrial S. cerevisiae xyloseconsuming strain TMB3400, which was constructed by expression of P. stipitis xylose reductase and xylitol dehydrogenase and overexpression of endogenous xylulose kinase in the industrial S. cerevisiae strain USM21.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 38 publications
3
43
0
1
Order By: Relevance
“…In the present investigation, HMF and furfural were completely metabolized by the strain before significant utilization of sugars started. This was also previously reported by others (Almeida et al 2008; Wan et al 2012) and indicates that S. stipitis CBS6054 is readily capable of converting HMF and furfural in the tested lignocellulose hydrolysate from sugarcane bagasse. Cell growth was highest (0.079 g/l/h) in hydrolysate containing mixed sugars and inhibitors such as acetate, HMF and furfural at concentrations of 3.2 ± 0.1, 0.4 and 0.5 g/l, respectively, indicating that the processing of bagasse hydrolysate under this condition will not inhibit the growth of S. stipitis .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present investigation, HMF and furfural were completely metabolized by the strain before significant utilization of sugars started. This was also previously reported by others (Almeida et al 2008; Wan et al 2012) and indicates that S. stipitis CBS6054 is readily capable of converting HMF and furfural in the tested lignocellulose hydrolysate from sugarcane bagasse. Cell growth was highest (0.079 g/l/h) in hydrolysate containing mixed sugars and inhibitors such as acetate, HMF and furfural at concentrations of 3.2 ± 0.1, 0.4 and 0.5 g/l, respectively, indicating that the processing of bagasse hydrolysate under this condition will not inhibit the growth of S. stipitis .…”
Section: Discussionsupporting
confidence: 89%
“…However, previous studies have shown arabinose is only utilized by S. stipitis for cell growth but not for ethanol production (Nigam 2001b). Furthermore, S. stipitis also has the natural ability to metabolize some of the sugar degradation compounds present in the hydrolysate after pretreatment (Almeida et al 2008; Wan et al 2012). The sensitivity of Scheffersomyces stipitis to inhibitors found in lignocellulose hydrolysate has been reported elsewhere (Bellido et al 2011; Delgenes et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…If this were the case, then this gene cluster would be downregulated because the adapted strains have a reduced consumption of xylose. However, given that xylose reductase has been demonstrated in aiding detoxiWcation processes, it is unlikely that downregulation would be advantageous for P. stipitis survival in a concentrated wood hydrolysate [2]. Therefore, it is doubtful that xylose reductase caused the observed change in xylose metabolism in P. stipitis RS01, RS02, and RS03.…”
Section: Carbohydrate Utilization Of Adapted Strainsmentioning
confidence: 96%
“…The xylose reductase has previously been established as an enzyme involved in detoxiWcation processes in P. stipitis and, therefore, may be related to changes observed in the adapted strains [2]. However, because there are multiple copies of the gene cluster encoding the xylose reductase gene (aldo/keto reductase) only a regulatory change would have resulted in the observed decrease in xylose utilization [13].…”
Section: Carbohydrate Utilization Of Adapted Strainsmentioning
confidence: 97%
“…The ability to use a wider array of the biomass feedstocks would help to decrease cost by reducing the number of upstream processing steps and by turning more of the biomass into biofuel. For example, S. cerevisiae has been engineered with the genes encoding xylose reductase (Xyllp) and xylitol dehydrogenase (Xyl2p) from Pichia stipitis to enable it to utilize xylose, the second most abundant carbohydrate in nature, as a carbon source for ethanol production [ 39]. However, simply overexpressing the genes led to low growth and fermentation rates due to redox imbalance.…”
Section: Production Hostmentioning
confidence: 99%